The Relapse of Gadamer and Heidegger into the Metaphysics of Art of the Young Nietzsche - Zúñiga García, José Francisco (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
Gadamer followed the footsteps of Heidegger in establishing the current known as philosophical hermeneutics. But Heidegger abandoned, after Being and Time, this way of thinking and considered since then that hermeneutics was Gadamer's ''concern". The article pro poses to show that Heidegger's abandonment relates to the acknowledgement of the impossibility of thinking about the transcendence of being starting from a transcendental project, and that Gadamer continues a philosophy with those characteristics that, nevertheless, aspires at the same time to be the heir of a thought that is no longer transcendental (that of the so-called «second Heidegger"). That apparent contradiction is resolved if it can be shown that the common root of both aspects presents important similarities with the young Nietzsche's metaphysics of art.
Keywords: Gadamer; Heidegger; Nietzsche; metaphysics; art; hermeneutics.